MAL Overexpression Leads to Disturbed Expression of Genes That Influence Cytoskeletal Organization and Differentiation of Schwann Cells. (5th September 2014) - Schmid, Daniela; Zeis, Thomas; Sobrio, Monia; Schaeren-Wiemers, Nicole
In the developing peripheral nervous system, a coordinated reciprocal signaling between Schwann cells and axons is crucial for accurate myelination. The myelin and lymphocyte protein MAL is a component of lipid rafts that is important for targeting proteins and lipids to distinct domains. MAL overexpression impedes peripheral myelinogenesis, which is evident by a delayed onset of myelination and reduced expression of the myelin protein zero ( Mpz / P0 ) and the low-affinity neurotrophin receptor p75 NTR . This study shows that MAL overexpression leads to a significant reduction of Mpz and p75 NTR expression in primary mouse Schwann cell cultures, which was already evident before differentiation, implicating an effect of MAL in early Schwann cell development. Their transcription was robustly reduced, despite normal expression of essential transcription factors and receptors. Further, the cAMP response element-binding protein (CREB) and phosphoinositide 3-kinase signaling pathways important for Schwann cell differentiation were correctly induced, highlighting that other so far unknown rate limiting factors do exist. We identified novel genes expressed by Schwann cells in a MAL-dependent manner in vivo and in vitro . A number of those, including S100a4, RhoU and Krt23, are implicated in cytoskeletal organization and plasma membrane dynamics. We showed that S100a4 is predominantly expressed by nonmyelinating Schwann cells, whereas RhoU was localized within myelin membranes, and Krt23 was detected in nonmyelinating as well as in myelinating Schwann cells. Their differential expression during early peripheral nerve development further underlines their possible role in influencing Schwann cell differentiation and myelination.